1999
DOI: 10.1046/j.1461-9563.1999.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in host susceptibility to attack by the mahogany shoot borer, Hypsipyla grandella (Zeller)

Abstract: 1 Attack by shoot borers (Hypsipyla grandella Zeller) is the main factor limiting the cultivation of Cedrela odorata and Swietenia macrophylla, two economically important members of the mahogany family. No viable methods of pest control are currently available. To assess for genetic variation in susceptibility to pest attack, a combined progeny/provenance test of C. odorata and a provenance test of S. macrophylla were established separately at CATIE, Turrialba, Costa Rica, and assessed intensively over an 84-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
3
25
1
4
Order By: Relevance
“…This is supported by observations of Costa et al (2013) who showed that Cedrela growing in southern Brazil exhibited regular cambial dormancy during the dry season, even in years when there was no water deficit, thus implying some conservatism in growth behaviour. Furthermore, providence trials (where seeds sourced from different origins are grown under the same conditions) have shown that Cedrela from drier sites show more pronounced leaf-fall behaviour than Cedrela from wetter sites, indicating that variation in phenology is at least partly controlled by phylogeny (Newton et al 1999). As Cedrela odorata is also known to have one of the highest levels of population differentiation of any tree species yet to be tested, with moist-and dryadapted lineages (Cavers et al 2003;Muellner et al 2009), it seems feasible that regional differences in ring periodicity might be associated with phylogenetic differences.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by observations of Costa et al (2013) who showed that Cedrela growing in southern Brazil exhibited regular cambial dormancy during the dry season, even in years when there was no water deficit, thus implying some conservatism in growth behaviour. Furthermore, providence trials (where seeds sourced from different origins are grown under the same conditions) have shown that Cedrela from drier sites show more pronounced leaf-fall behaviour than Cedrela from wetter sites, indicating that variation in phenology is at least partly controlled by phylogeny (Newton et al 1999). As Cedrela odorata is also known to have one of the highest levels of population differentiation of any tree species yet to be tested, with moist-and dryadapted lineages (Cavers et al 2003;Muellner et al 2009), it seems feasible that regional differences in ring periodicity might be associated with phylogenetic differences.…”
Section: Resultsmentioning
confidence: 99%
“…En este sentido, Sánchez et al (2003) encontraron variación en cuanto a parámetros de crecimiento en C. odorata de diferentes procedencias de México. Así mismo, hay evidencia en los ensayos de progenie y procedencia que indican que algunos genotipos muestran diferentes niveles de tolerancia al ataque del barrenador (Newton, Leakey, & Mesean, 1993, Newton, Cornelius, Mesen, & Leakey, 1995Newton et. al., 1999).…”
Section: Discussionunclassified
“…However, the lower Amerindian density, the large distances between the main settlements, the prevalence of a hunter-gatherer subsistence strategy in many groups, and the management of the landscape using agricultural systems that did not require intensive forest clearance (Denevan, 2001, Balée 2006 In addition to providing genetic evidence of regional demographic history, our study should also be useful for genetic conservation and management. In mahogany, important traits such as resistance to shoot borers, growth rate and degree of branching show heritable variation (Newton et al, 1999). The deep phylogeographic break between Central and South American mahogany populations suggests that there may be major genomic differences between these sources of mahogany.…”
mentioning
confidence: 99%